Ogilvie's syndrome presented with delirium in an older lady with corticobasal syndrome. Issue 5 (October 2021) - Mutlay, Feyza; Kaya, Derya; Isik, Ahmet Turan
Abstract: Objective: Corticobasal syndrome (CBS) is one of an atypical parkinsonian syndromes characterized by extrapyramidal features as well as cortical involvement signs. A variety of factors may lead to delirium in older adults with chronic progressive life-limiting neurological illnesses like CBS. Ogilvie's syndrome (OS) is an acute colonic pseudo-obstruction in which abdominal distension, nausea, vomiting, and constipation can be seen. We report a case of OS identified as the underlying possible cause of delirium in an 80-year-old woman with CBS. We also discuss the importance of holistic approach which is essential to manage the underlying cause and to preserve the quality of life in particular for the frail geriatric population who potentially needs palliative care or already benefits from palliative care. Method: An older patient with CBS presented with symptoms similar to that of acute colonic obstruction and subsequently developed delirium. The patient was found to have colonic pseudo-obstruction (OS). Result: Neostigmin infusion was therefore given to treat it and delirium was resolved. Significance of results: To the best of our knowledge, clinical manifestation of delirium as OS in a patient with CBS has not been previously reported. OS may be superimposed to CBS in older patients, and OS in such patients may play a role as a precipitating factor for the development of delirium. Given the fact that CBS is progressive and rare neurodegenerative disease and almost all of these patients need palliative care, eventually, health-care professionals, especially in palliative care, should be aware of distinctive challenges of life-limiting chronic neurological illnesses, such as conditions that may lead to the development of acute colonic pseudo-obstruction because the rapid treatment of them prevents the use of potentially harmful drugs, surgical procedures, or inappropriate interventions.